2011
DOI: 10.1371/journal.pone.0027980
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of the ESX-1 Region of Mycobacterium tuberculosis: Insights into the Mechanism of Type VII Secretion System

Abstract: Type VII secretion system (T7SS) is a recent discovery in bacterial secretion systems. First identified in Mycobacterium tuberculosis, this secretion system has later been reported in organisms belonging to the Actinomycetales order and even to distant phyla like Firmicutes. The genome of M. tuberculosis H37Rv contains five gene clusters that have evolved through gene duplication events and include components of the T7SS secretion machinery. These clusters are called ESAT-6 secretion system (ESX) 1 through 5. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 60 publications
0
30
0
1
Order By: Relevance
“…Like other ESAT-6 proteins, the structure of the N-terminal domain of EspA is predicted to comprise two alpha-helices in a hairpin conformation separated by the W-X-G motif. This conformation was hypothesized to be important for interaction of EspA with EspC, encoded by the second gene in the espACD operon (17), although such an interaction has not yet been detected despite considerable effort (10,12,14). Nevertheless, the EspA W55R and EspA G57R mutants were indeed defective for ESAT-6 and CFP-10 secretion and were attenuated for virulence in cellular models of infection and in acute infection in mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like other ESAT-6 proteins, the structure of the N-terminal domain of EspA is predicted to comprise two alpha-helices in a hairpin conformation separated by the W-X-G motif. This conformation was hypothesized to be important for interaction of EspA with EspC, encoded by the second gene in the espACD operon (17), although such an interaction has not yet been detected despite considerable effort (10,12,14). Nevertheless, the EspA W55R and EspA G57R mutants were indeed defective for ESAT-6 and CFP-10 secretion and were attenuated for virulence in cellular models of infection and in acute infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that substrates of the type VII ESX secretion system either have the Y-XXX-D/E motif or are secreted complexed to substrates carrying the motif (16). In addition, the ESAT-6 WXG100 family of proteins, which includes ESAT-6 and CFP-10, possess a conserved W-X-G motif located in the middle of the protein (3,9,17). Structural and biochemical studies have shown that the W-X-G motif in ESAT-6 is situated in a loop linking the two alpha-helices of the protein, and a hairpin conformation of these two helices is impor-tant for heterodimerization with CFP-10 (18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the ESX-1 secretion system has stimulated considerable research interest, especially in light of its potential as a drug target (1). ESX-1 is the prototype of type VII secretion systems found in some Grampositive bacteria (1,2), and the ESX-1 substrate ESAT-6 is a major virulence factor, implicated in diverse host-pathogen interactions (1,3), including host cell lysis (4,5), T cell inhibition (6), and activation of macrophage inflammasomes (7,8). The protein CFP10 is cosecreted with ESAT-6, forming a 1:1 complex, and interacts with the secretion apparatus (9)(10)(11).…”
mentioning
confidence: 99%
“…It is possible that known proteins integral to the MOM promote the transit of proteins across the envelope. For example, in silico analyses have suggested that Mce1 family proteins, which have a role in lipid homeostasis and transport, may promote ESX-1-mediated translocation across the MOM (130,155,156). The proposed link between the Mce1 proteins and ESX-1 is based on phylogenetic profiles, predicted protein-protein relationships, and analyses suggesting the Mce proteins may be MOM pore-forming proteins (155).…”
Section: Crossing the Envelopementioning
confidence: 99%